Kānprayuk chai rabop sārasonthēt phūmisāt phư̄a kānwikhro̜ læ wāngphǣn čhatkān phư̄nthī sīang phai din thalom læ nam pā lailāk : kō̜ranī sưksā ʻAmphœ̄ Mư̄ang Lop Burī, ʻAmphœ̄ Bān Mī, læ ʻAmphœ̄ Khōk Samrōng, Čhangwat Lop Burī (Samnak Wičhai læ Khwāmrūammư̄ Rawāng Prathēt, Sūn Thēknōlōyī Sārasonthēt, Krom Pō̜ngkan læ Banthao Sāthāranaphai, 2010)
Application of remote sensing and Geographic Informaion System to monitor, analyze, and plan for landslides and sudden floods in Lop Buri Province, Central Thailand.